Analisis Kesiapan Kerja Mahasiswa Tingkat Akhir Prodi Pendidikan Teknik Elektro Universitas Negeri Padang - Rifan Pratama; Sukardi Sukardi (Journal of Electrical Vocational Education, 2025)
Abstract—Graduate employability has become a significant challenge in today’s global job market, especially for students in vocational programs such as Electrical Engineering Education. The persistent mismatch between graduates' competencies and industry demands highlights the need to evaluate students’ readiness for the workforce. This study aims to analyze the work readiness of final-year students in the Electrical Engineering Education Program at Universitas Negeri Padang using a descriptive quantitative approach. This method was employed to describe the current state of work readiness based on questionnaire data that had been tested for validity and reliability. The questionnaire was distributed to final-year students to gather their perceptions of their readiness to enter the workforce. The findings show that the students’ level of work readiness falls into the “moderate” category. Most students have clear career plans and sufficient internship experience, although the relevance of these experiences to industry needs remains limited. Additionally, aspects such as learning motivation, mastery of soft and hard skills, and self-competence still need further development. None of the respondents felt “very ready,” indicating that their overall readiness is not yet optimal. Therefore, improvement is needed through more relevant internships, structured soft skills training, intensive career guidance, and stronger collaboration with industry. These efforts are expected to enhance students’ preparedness to face the dynamic and competitive labor market.